Efeito do ácido clorogênico, cafeina e café em parâmetros bioquimicos e comportamentais em ratos diabéticos - Stefanello, Naiara (2012)
Studies have shown that the hyperglycemia in diabetes leads to complications in cognitive, physiological and structural central nervous system (CNS) mainly linked with increased production of reactive oxygen species (ROS), which contribute to the development of chronic complications of the diabetic state. Chlorogenic acid is a phenolic compound found in coffee that presents antioxidant, neuroprotective and hypoglycemic function. In addition, caffeine is also found in high concentrations in coffee and is known for its antioxidant, neuroprotective effects and psycho-stimulant. The objective of this study was to evaluate the effect of chlorogenic acid (CGA), caffeine (CA) and coffee (CF) in acetylcholinesterase (AChE), Na+,K+-ATPase and Aminolevulinate acid dehydratase (δ-ALA-D) activities, as well as lipid peroxidation levels (TBARS) from cerebral cortex, memory and anxiety on strepzotocin (STZ)-induced diabetic rats. The animals were divided into eight groups (n=6 13): Control; Control/CGA 5 mg/kg; Control/CA 15 mg/kg; Control/CF 0.5 g/kg; Diabetic; Diabetic/CGA 5 mg/kg; Diabetic/CA 15 mg/kg e Diabetic/CF 0.5 g/kg. Two-nine days after treatment with compounds, the animals were submitted to behavioral tests (Inhibitory avoidance and elevated plus maze) and then sacrificed and the cerebral cortex was collected. Our results demonstrated that AChE activity and TBARS levels were increased in cerebral cortex, while δ-ALA-D and Na+, K+-ATPase activities were decreased in the diabetic rats when compared to the control group. Furthermore, the diabetic rats showed deficit in memory and an increase in the anxiety. There was prevention in the increase of AChE activity when diabetic rats were treated with CGA and CA when compared with untreated rats. CGA, CA and Coffee intake restored partially cerebral δ-ALA-D and Na+, K+-ATPase when compared to untreated diabetic group. Moreover, CGA prevented diabetes-induced TBARS production and improve the memory and decrease the anxiety. Our results showed that CGA, CA and coffee can modulate cerebral oxidative stress and δ-ALA-D and Na+, K+-ATPase activity in a model of diabetes type I. Consequently, we can suppose that these compounds mainly the CGA, which has the better effect, could modulate this enzymes in CNS that are altered in diabetes.